Evaluation of Community Pharmacists Knowledge, Attitude and Practice towards Modified Release Dosage Forms(Conference Paper )# - Albassam, Noor Yousif; Mohammed, Amenah; Murtada, Suhair (Iraqi Journal of Pharmaceutical Sciences, 2022)
Purpose:To evaluate knowledge, practice and attitude of community pharmacists in Basra regarding modified release dosage forms which are widely used for many therapeutic purposes in pharmacy practice.Methods:The current study was conducted among certified pharmacists in Basra governorate- south of Iraq. Data collection was carried out by a questionnaire.Results:A total number of 175 community pharmacists responded to the questionnaire. The majority worked in OTC based dispensing pharmacies located in the center of the city. Most respondents missed K1 and were unable to state the difference between different types of modified products. There was a major positive agreement towards medical representatives' rule in promoting the prescribing of modified release products by physicians. Avoiding crushing and breaking of solid oral modified release drugs were identified by the majority of participants. Correlation analysis showed a 22.8 correlation coefficient between knowledge and attitude which was statistically significant. Males showed statistically significant higher knowledge and practice scores than females.Conclusions:The conduction of a brief educational program would be very beneficial in bringing basic theoretical knowledge with practicing points of interest and promote a more positive attitude toward this unique class of novel drug delivery system.